Representasi Tindakan Kepahlawanan (Analisis Semiotika Iklan Grab – Pahlawan Top Up) - Shella, Grace; Sukendro, Gregorius Genep (Prologia, 2023)
Development of technology has an impact on changes in the lifestyle of people who tend to be active in the internet world. In today's era, the internet has become an important thing to increase people's awareness. Grab is a transportation service application that can be downloaded via smartphones. Grab creates a unique ad design to attract customers to market their products. Interesting ads can be seen only through combining all existing things and creating new things, but advertisements that are formed as creatively as possible so that consumers collect and focus on the message of the ad. The author's purpose of conducting research is to determine the representation of heroic actions in the Grab – Pahlawan Top Up advertisement using Charles Sander Peirce's semiotics which focuses on signs, objects and interpretants. This research uses a descriptive approach. The results of this study, contained the meaning of heroic actions in the Grab - Pahlawan Top Up advertisement, namely courage, willingness to sacrifice, sincerity shown by Grab partners. Pesatnya perkembangan teknologi, berdampak pada perubahan gaya hidup masyarakat yang cenderung semakin aktif di internet. Saat ini, internet menjadi hal penting untuk meningkatkan kesadaran masyarakat. Grab adalah aplikasi daring layanan transportasi yang dapat diunduh melalui ponsel pintar. Grab membentuk desain iklan yang unik dalam menarik pelanggannya untuk memasarkan produk. Iklan yang menarik dapat dilihat tidak hanya melalui menggabungkan semua hal yang ada dan menciptakan hal yang baru, melainkan iklan dibentuk sekreatif mungkin sehingga konsumen ingat dan fokus akan pesan dari iklan tersebut. Penelitian ini bertujuan mengetahui representasi tindakan kepahlawanan dalam iklan Grab – Pahlawan Top Up menggunakan semiotika Charles Sander Peirce yang berfokus pada tanda, objek dan Interpretatif. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Berdasarkan hasil penelitian ini, terkandung makna tindakan kepahlawanan dalam iklan Grab – Pahlawan Top Up yaitu keberanian, rela berkorban, tulus yang ditampilkan oleh mitra Grab.